{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

# exam3 - Granillo Yvette Exam 3 Due Dec 1 2005 11:00 pm Inst...

This preview shows pages 1–3. Sign up to view the full content.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Granillo, Yvette Exam 3 Due: Dec 1 2005, 11:00 pm Inst: Edward Odell 1 This print-out should have 18 questions. Multiple-choice questions may continue on the next column or page find all choices before answering. The due time is Central time. 001 (part 1 of 1) 10 points Find f ( x ) when f ( x ) = 7 cos x- 2 sin x and f (0) = 3. 1. f ( x ) = 7 cos x + 2 sin x + 10 2. f ( x ) = 7 sin x + 2 cos x- 4 3. f ( x ) =- 7 sin x + 2 cos x + 1 4. f ( x ) = 7 cos x + 2 sin x- 4 5. f ( x ) =- 7 cos x + 2 sin x + 10 6. f ( x ) = 7 sin x + 2 cos x + 1 correct Explanation: Since d dx sin x = cos x, d dx cos x =- sin x, we see immediately that f ( x ) = 7 sin x + 2 cos x + C with C an arbitrary constant. The condition f (0) = 3 determines C : f (0) = 3 = 2 + C = 3 since sin 0 = 0 , cos 0 = 1 . Consequently, f ( x ) = 7 sin x + 2 cos x + 1 . keywords: Stewart5e, 002 (part 1 of 1) 10 points If the graph of f is the bold horizontal line shown in black in x y which one of the following contains only graphs of anti-derivatives of f ? 1. x y correct 2. x y 3. x y 4. x y Granillo, Yvette Exam 3 Due: Dec 1 2005, 11:00 pm Inst: Edward Odell 2 5. x y Explanation: If f ( x ) = m is a constant function, then its most general anti-derivative F is of the form F ( x ) = mx + C with C an arbitrary constant. Thus the graph of F is a straight line having slope m , and so the family of anti-derivatives of f ( x ) = m consists of all parallel lines, each having slope m . Now for the given f ( x ) = m , clearly m &amp;lt; 0. Consequently, only x y consists entirely of graphs of anti-derivatives of f . keywords: Stewart5e, 003 (part 1 of 1) 10 points Find the value of f (- 1) when f 00 ( t ) = 6( t + 1) and f (1) = 5 , f (1) = 3 . 1. f (- 1) = 10 2. f (- 1) = 11 3. f (- 1) = 12 4. f (- 1) = 9 correct 5. f (- 1) = 8 Explanation: The most general anti-derivative of f 00 has the form f ( t ) = 3 t 2 + 6 t + C where C is an arbitrary constant. But if f (1) = 5, then f (1) = 3 + 6 + C = 5 , i.e., C =- 4 . From this it follows that f ( t ) = 3 t 2 + 6 t- 4 . The most general anti-derivative of f is thus f ( t ) = t 3 + 3 t 2- 4 t + D , where D is an arbitrary constant. But if f (1) = 3, then f (1) = 1 + 3- 4 + D = 3 , i.e., D = 3 . Thus f ( t ) = t 3 + 3 t 2- 4 t + 3 , and so f (- 1) = 9 . keywords: Stewart5e, 004 (part 1 of 1) 10 points A trailer rental agency rents 12 trailers per day at a rate of \$40 per day. It discovers that for each \$5 increase in rate, one fewer trailer is rented. Determine the the maximum income, I max , the rental agency can obtain....
View Full Document

{[ snackBarMessage ]}

### Page1 / 9

exam3 - Granillo Yvette Exam 3 Due Dec 1 2005 11:00 pm Inst...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online